Endosphere Microbiome and Metabolic Differences Between the Spots and Green Parts of Tricyrtis macropoda Leaves - Wang, Yan; Cheng, Huyin; Chang, Fan; Zhao, Le; Wang, Bin; Wan, Yi; Yue, Ming (Frontiers in Microbiology, 2021)
Background. Plant leaves are important organs for photosynthesis and biological energy production. The leaves of Tricyrtis macropoda have an unusual spotted pattern. However, whether the spots of T. macropoda affect the plant microbiome and metabolites is unclear. In this study, we compared differences in the endosphere microbiome and plant metabolites in green parts and spots and the effects of spots on the photosynthesis of leaves. Methods. 16S/ITS sequences and metabolite spectra were obtained by high-throughput amplicon sequencing and ultra-high-performance liquid chromatography-high-resolution mass spectrometry, respectively. Changes in the diversity of the endophytic microbial community and metabolites were studied, and the effect of T. macropoda leaf spots on photosynthesis was examined by chlorophyll fluorescence. Results. The results showed that the relative abundance of Cercospora fungi in the leaf spots of T. macropoda was significantly higher than that in the green parts (P < 0.05) while Colletotrichum fungi showed low abundance in the spots. Alkaloid and ketone metabolites were decreased in the green parts compared with the spots, and amino acids, organic acids, lipids and other compounds were increased in the green parts compared with the spots. A combined analysis of microbial communities and metabolites showed a significant correlation between the endophytic fungal communities and metabolite production. The changes in these metabolites may cause changes in local leaf colour. In addition, we found that the spot areas of T. macropoda can be photosynthetically normal. Conclusion. This research showed the relationship between endophytic microorganisms and metabolites, and the findings advance our understanding of endophyte-plant interactions and provide a new direction for investigating the relationship between endophytes and phenotypes.